2016
DOI: 10.1038/ni.3463
|View full text |Cite|
|
Sign up to set email alerts
|

A TRAF-like motif of the inducible costimulator ICOS controls development of germinal center TFH cells via the kinase TBK1

Abstract: Inducible costimulator (ICOS) signaling fuels the stepwise development of T follicular helper (TFH) cells. However, a signaling pathway unique to ICOS has not been identified. We show that TANK-binding kinase 1 (TBK1) associates with ICOS via a conserved motif, IProx, which shares homology with tumor necrosis factor receptor (TNFR)-associated factors, TRAF2 and TRAF3. Disruption of this motif abolishes the association with TBK1, thus identifying a TBK1-binding consensus. Mutation of this motif in ICOS, or depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 55 publications
(93 reference statements)
1
70
2
Order By: Relevance
“…S1E, as previously described (Zheng et al, 2009). Nevertheless, given the moderate effect on Tfh differentiation by shRNA-mediated knockdown of ICOS expression (Pedros et al, 2016), it is unlikely to fully explain the marked Tfh defect of Irf4 −/− cells. Thus, besides T cell activation, Irf4 likely plays an essential role in regulating the differentiation of Tfh cells.…”
Section: Resultsmentioning
confidence: 99%
“…S1E, as previously described (Zheng et al, 2009). Nevertheless, given the moderate effect on Tfh differentiation by shRNA-mediated knockdown of ICOS expression (Pedros et al, 2016), it is unlikely to fully explain the marked Tfh defect of Irf4 −/− cells. Thus, besides T cell activation, Irf4 likely plays an essential role in regulating the differentiation of Tfh cells.…”
Section: Resultsmentioning
confidence: 99%
“…The potent activation of Akt may explain, in part, the enhanced T cell persistence of ICOS-based CAR T cells, as Akt is a known T cell survival factor. Although PI3K is the main signaling molecule that is known to interact with ICOS, it has been recently reported that the cytoplasmic tail of ICOS has 2 potentially novel evolutionary conserved motifs (49). The ICOS proximal motif is homologous to a conserved motif found in the TNFR-associated factors TRAF2 and TRAF3, and it binds to the kinase TBK1 (49).…”
Section: Discussionmentioning
confidence: 99%
“…Although PI3K is the main signaling molecule that is known to interact with ICOS, it has been recently reported that the cytoplasmic tail of ICOS has 2 potentially novel evolutionary conserved motifs (49). The ICOS proximal motif is homologous to a conserved motif found in the TNFR-associated factors TRAF2 and TRAF3, and it binds to the kinase TBK1 (49). How these ICOS-specific motifs contribute to the observed phenotype of ICOS-based CAR T cells is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Other than known PI3K binding motif Tyr-x-x-Met (YxxM, where ‘x’ indicates any amino acid) of ICOS, Pedros et al using SILAC (stable isotope labeling) approach showed that ICOS cytoplasmic tail has other two conserved motifs, one Proximal SSSVHDPNGE (IProx) and second AVNTAKK motif. Retroviral transduction of CD4 + T cells (TCR transgenic for LCMV peptide gp 61–80) with ICOS mutant in PI3k-binding site of IProx motif and adoptive transfer into ICOS −/− mice and then LCMV infection fail to generate Tfh cells illustrating that IProx plays a critical positive role in Tfh differentiation (73). Importantly, IProx motif has homology with the conserved sequences with TRAF2 and TRAF3.…”
Section: Cytokine As Positive and Negative Regulators Of Tfh Differenmentioning
confidence: 99%